THE PERIODONTAL EFFECTS OF AN OPTIMAL INTRUSIVE FORCE ON A MAXILLARY CENTRAL INCISOR. A FEM EVALUATION - Ionuț Luchian; Ioana Vâță; Ioana Mârțu; Cristel Stirbu; Sioustis Ioana; Monica Tatarciuc; Silvia Mârțu (Romanian Society of Oral Rehabilitation, 2016)
Introduction. Proffit's experience shows that orthodontic treatment is an option even after severe periodontal problems occurred. He claims that if an optimal control of the periodontal condition is maintained then we will not experience any additional bone loss. Although the exact magnitude of the orthodontic forces is difficult to be determined in clinical practice, the literature recommends around 0.2 N as an optimal value for an intrusive force. Material and method.We used FEM Catia V5R16 software in order to create an accurate model of a maxillary arch and of an upper central incisor.The upper central incisor was designed in such a way that it will respect in the smallest details the real characteristics.We applied and optimal intrusive force with the magnitude of 0.25 N at the level of maxillary central incisor with no periodontal disease. Results and discussion.We can remark that under the effect of an oprimal force, σ ech inside the complex toothPDL-alveolar bone is similar both for the case with no periodontal disease and for the one with 33% HBL.The tension on the direction of the force (σ c) shows a very light inscrease of 5,97% in the case of 33% HBL compared to the case of no HBL.Analyzing the results of the tooth movement (f) registered during loading with a 0,25 N intrusive force, we can state that f stays constant in the case of no HBL and in the case of 33% HBL. Conclusions.Intrusion of maxillary central incisors using an optimal force showed to be a strong alternative of treatment in the periodontal cases.